Cities for global health - Ezzati, Majid; Webster, Christopher J; Doyle, Yvonne G; Rashid, Sabina; Owusu, George; Leung, Gabriel M (The BMJ, 2022)
This article was published in The BMC [2018 Open Access ] and the definite version is available at: https://doi.org/10.1136/bmj.k3794 The Journal's website is at: https://www.bmj.com/content/363/bmj.k3794